Le paradis de Gianni Celati - Pascaline Nicou (Parole Rubate, 2018)
Lunario del paradiso (1978) by Gianni Celati is the final book of the Parlamenti buffi trilogy, which is inspired by the cantiche of the Commedia. This paper discusses Celati’s text as a parody of the Commedia. The young Antje embodies Beatrice and the Paradise is transformed into the illumination of a grotesque electric light, while the protagonist’s journey comically repeats Dante's mission model.